Visualization of Incisive Foramen in Intraoral Periapical Radiographs- A Comparative Radiographic Study - Niroula, Deepa; Poudel, Kalpana; Dahal, Sirjana; KC, Krishna (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: Incisive foramen, a normal anatomical landmark in the anterior maxilla, appears as a radiolucency between the apices of the maxillary central incisors on intraoral periapical radiographs. This study was conducted to compare the visibility of the incisive foramen in between bisecting-angle and paralleling techniques. Methods: An analytical cross-sectional study was conducted among 100 patients selected by consecutive sampling method. Group 1 included patients with 50 radiographs obtained for visualization of incisive foramen using bisecting angle technique and Group 2 included 50 patients with radiographs using paralleling technique. Data was entered into Microsoft Excel Sheet and analyzed in SPSS version 24. Chi square/fisher’s exact test was done to determine the proportional difference between visualization of incisive foramen by using two techniques. The significance level was set at P<0.05. Results: The incisive foramen was visible in 74 (74%) radiographs with a higher proportion of visible foramen observed in paralleling techniques. A statistically significant association was observed between age and visibility of the incisive foramen (p = 0.016) such that <35 years aged patients showed a higher proportion of visible incisive foramen (65.6%) compared to those aged 35–59 years (23.1%). However, more visualization was seen in the ≥60 years age group (80.0%). Significant association between the radiographic technique used and the visibility of the incisive foramen was seen (P< 0.001). Conclusion: The findings of this study revealed better visualization of incisive foramen using paralleling technique than bisecting angle technique suggesting that paralleling technique should be preferred in routine periapical radiography of the anterior maxilla to improve visualization of the incisive foramen.